Association of blood urea nitrogen to serum albumin ratio with arterial stiffness in type 2 diabetes patients: a Chinese cross-sectional study - He, Shengqing; Meng, Wanrui; Huang, Miaoling; Fu, Qingsong; Shen, Jie (Frontiers in Endocrinology, 2025)
BackgroundArterial stiffness is an early indicator of atherosclerosis. The blood urea nitrogen to serum albumin ratio(BAR) is associated with poor prognosis in several chronic diseases. However, the relationship between BAR and arterial stiffness in type 2 diabetes mellitus (T2DM) patients has not been extensively studied. This study aimed to examine the relationship between BAR and brachial-ankle pulse wave velocity (baPWV), an indicator of arterial stiffness in patients newly diagnosed with T2DM.MethodsA total of 510 adult patients newly diagnosed with T2DM were enrolled between January 2021 and December 2023. BAR was calculated by blood urea nitrogen/albumin ratio. A baPWV ≥1400 cm/s was defined as arterial stiffness. A linear regression model and logistic regression model were used to assess the relationship between BAR and baPWV after adjusting for potential confounders.ResultsThe average age of the patients in this study was 45.66 ± 10.18 years, and 78.8% were male. The mean baPWV was 1469.15 ± 295.82 cm/s, and 50.8% of patients exhibited arterial stiffness. The prevalence of arterial stiffness increased significantly across ascending BAR tertiles (T1: 39.3%, T2: 51.7%, T3: 61.4%; p = 0.002). Linear correlation analysis revealed a positive correlation between BAR and baPWV. According to the fully adjusted logistic regression model, each unit increase in the lnBAR was associated with a 3.452-fold greater risk of arterial stiffness[95% CI(1.586, 7.513), p = 0.002]. Compared to the lowest tertile (T1), participants in the middle (T2) and highest (T3) BAR tertiles had a significantly greater risk of arterial stiffness [T2: OR = 1.915, 95% CI (1.016, 3.609), p = 0.044; T3: OR = 2.064, 95% CI (1.051, 4.054), p = 0.035]. Stratified analyses demonstrated consistent positive correlations between BAR and baPWV across sex and BMI subgroups, as well as in individuals aged < 50 years.ConclusionBAR levels were independently and positively correlated with baPWV in Chinese patients with newly diagnosed T2DM.